Behavior of RC building columns under cyclic loading: Experimental study - Hugo Rodrigues (2012)
An experimental campaign is underway in order to understand the behavior of rectangular columns under uniaxial and biaxial flexure. The present paper addresses the initial part of that campaign, by reporting on two columns tested under uniaxial bending in one horizontal direction and then submitted to another uniaxial test in the other direction. The test result analysis focuses on the contributions of flexure, shear and slip components to the global deformation. The experimental results were compared with a simplified method for column response. The Park and Ang damage index is calculated and compared with the physical damage observed.